Earning Trust through Performance: The Initiation Mechanism of Collaborative Governance in Low-Trust Communities - Yijia Wu (International Journal of Social Sciences and Public Administration, 2026)
In low-trust communities, residents often expect visible service improvements before paying fees, whereas property management companies require stable revenue expectations before increasing investment. This mutual wait-and-see stance creates a first-mover dilemma. Drawing on the fiduciary property management reform in XH Residential Community in Chengdu, this study uses semi-structured interviews, participant observation, and document analysis to examine how institutional transparency is converted into performance-based trust. The findings show that the reform first reduced uncertainty through a collectively owned fund, open budgeting, and financial oversight. The property management company then assumed initial risk by advancing funds, thereby sending a credible signal of sustained contract performance. Environmental improvements, facility repairs, and public disclosure of results converted institutional commitments into observable governance performance, prompting residents to revise their assessment of the company and respond through fee payment, oversight, and participation. As performance feedback continued, one-off trust building developed into relatively stable expectations of cooperation. The initiation of cooperation in low-trust communities therefore depends not only on transparent rules but also on a mechanism that combines first-bearing of risk with visible performance.